The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.jcrs.2007.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Ingress of bacterial inoculum into the anterior chamber after bimanual and microcoaxial phacoemulsification in rabbits

Abstract: Bacterial ingress occurred in both groups, although it was statistically significantly higher in the bimanual group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…15,16 The disadvantages of biaxial MICS include anterior chamber instability, limitations of vacuum levels, 1,2 and potential trauma caused by the mechanical and thermal impact on the wound. [17][18][19][20] Microcoaxial phacoemulsification has the advantages of standard coaxial phacoemulsification and, unlike biaxial MICS, does not have a steep learning curve. 3 The main disadvantage of the technique is the decreased followability of the nucleus, which can increase turbulence and reduce efficacy.…”
mentioning
confidence: 99%
“…15,16 The disadvantages of biaxial MICS include anterior chamber instability, limitations of vacuum levels, 1,2 and potential trauma caused by the mechanical and thermal impact on the wound. [17][18][19][20] Microcoaxial phacoemulsification has the advantages of standard coaxial phacoemulsification and, unlike biaxial MICS, does not have a steep learning curve. 3 The main disadvantage of the technique is the decreased followability of the nucleus, which can increase turbulence and reduce efficacy.…”
mentioning
confidence: 99%
“…We further speculate that in the bimanual group, the increased ingress of trypan blue could be due to wound distortion resulting from tight geometry of the incision. 21 We believe this could be due to the tightness of the incision, which may have resulted in oar-locking. Moreover, the absence of the shielding effect of the sleeve may have adversely affected the integrity of the incision, thereby accelerating increased trypan blue ingress.…”
Section: Discussionmentioning
confidence: 96%
“…The coaxial tube combines a stainless steel pipe called the 'tip' and a silicon tube called the 'sleeve', which coaxially surrounds the tip and where the gap between the tip and sleeve provides the irrigation flow. Generally, bimanual phacoemulsification has the advantage of small incision sites (individually 1.2 mm-1.4 mm in length) in comparison to a relatively large incision (1.8 mm-3.2 mm) in coaxial phacoemulsification (Gajjar et al 2007;). Coaxial phacoemulsification, however, has advantages of a single incision site, better temperature control, easier handling, better sealability, and several fluidic benefits (Osher and Injev 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Coaxial phacoemulsification, however, has advantages of a single incision site, better temperature control, easier handling, better sealability, and several fluidic benefits (Osher and Injev 2007). Even though both types of phacoemulsification offer advantages and are still in use, it has been reported that bimanual phacoemulsification has more disadvantages such as limited infusion of the irrigation solution (Osher and Injev 2007), chamber instability caused by leakage at the two incision sites (Gajjar et al 2007;), higher possibility for bacteria to enter through the multiple incisions (Gajjar et al 2007), and regular occurrence of physical wound trauma due to tight angular movement of the instrument through the small incisions ).…”
Section: Introductionmentioning
confidence: 99%